Application of the TPACK approach to improve science learning outcomes in grade VI elementary school - Mandailina, Vera; Oktyawati, Mega; Laksmi Nusa Rinjayani, Dewi; Hartika, Lina; Lailatul Hikmah, Wahyu (Jurnal Bidang Pendidikan Dasar, 2024)
The purpose of this research is to describe the improvement of learning outcomes in grade VI students of Primary school 15 Ampenan through the TPACK approach. This research uses descriptive quantitative data analysis type, with classroom action research method, this research was conducted in two cycles, with a total of 13 students. Each cycle consists of action planning, observation, and reflection. Data collection techniques using tests. The results showed student learning outcomes in cycle I with a percentage of 69% learning completeness or 9 students who reached the minimum completeness criteria out of 13 students and in cycle II presentation of learning completeness of 85% or 11 students out of 13 the total number. The results of this study are expected to be used as a reference by teachers at school to apply the TPACK approach.